Automation of the rapid plasma reagin test using the Autotape System. Issue 2 (February 1977) - Booth, J R; Sequeira, P J; Wagstaff, W; Hopkinson, I; Gibbs, D; Bennett, E
Abstract : The paper describes the Autotape System, a new piece of apparatus which is automated slide testing equipment, and its successful application to the rapid plasma reagin test.